Jet Web - Eckardt, Dietrich. author. aut Link
XX, 738 p. 257 illus.
Keywords: The present book describes the development history of turbojet engines, mainly in the web-type triangle Great Britain (USA) - Germany - Switzerland from early beginnings in the 1920s up to the first practical usage in the 1950s, before the still unbroken, grand impact of aero propulsion technology on global air traffic started. interconnections are highlighted, including the considerable impact of axial-flow compressor design know-how of the Swiss/German company BBC Brown Boveri & Cie. on both sides. The author reveals significant undercurrents which led to a considerable exchange, and thus change in understanding of the technical-historical perspective, especially in the decisive years before WWII, and thus closes gaps in the unilateral views of this ground-breaking technical advancement. The old ‘Whittle vs. von Ohain Saga’ is not repeated in full, but addressed in sufficient detail to understand the considerably enlarged narrative scope. TheTarget Groups Specialists in aviation technology and jet engines as well as technology historians Interested beginners with some mechanical engineering background The Author Prof. Dr.-Ing. Dietrich ECKARDT has more than forty years of professional experience in turbomachinery research, in German turbojet engine and Swiss power generation gas turbine industry. He is winner of the 2017 ASME engineer-historian award. The Answer to a Frequently Asked Question ‘German historians are not easily moved to ... praise German science, technology and industry, not because Germany lost the war, but because those have been contaminated to their very core by the crimes of the Nazi regime. To always remind of the crimes whenever achievements are pointed out has become a specific art of German historians which has resulted in a number of methodological and theoretical innovations. ...Thus we have created a history of German science, technology and industry which is less shining and less glamorous, sometimes of a German thoroughness, but cautiously depicted and balanced.’ Professor Dr. Lutz Budrass, Historisches Institut der Ruhr-Universität Bochum.